Influence of volume container in the production of rhizomes in Seemannia (Gesneriaceae) - Bologna, Paula; Stancanelli, Santiago (Sociedade Brasileira de Floricultura e Plantas Ornamentais, 2021)
Seemannia Regel belongs to the Gesnereacieae family. It is an herbaceous perennial plant with colorful and brilliant flowers that produces fleshy scaly rhizomes with axillary dormant buds. The objective of this study was to evaluate the effect of the volume of the container in the production and the quality of the rhizomes. Plants of a select hybrid of Seemnania were used. Three volume of container were tested: v1 of 1 L, v2 of 1,5 L and v3 of 2 L. Plants were cultivated in the containers following a conventional management. Dry matter, production (number and weight of rhizomes) and quality of the rhizomes were recorded. The rhizomes were classified into four qualities (A, B, C, D) according to the length and width, and the number of the scales. All data was subject to statistical analysis. Dry matter, weight and number of rhizomes increased as the volume of container increased. The v3 container recorded the highest values for these three parameters. Major volume of container, major was the development of vegetative mass and consequently the number and the weight of rhizomes were higher. In regard to the qualities of the rhizomes, v1 and v3 treatments had a better proportion of A rhizomes (the bigger size) compared to v2 treatment. The knowledge of the rhizome quality can be useful to the growers in order to select the best rhizome size for a good production. The v3 treatment recorded the highest number of A rhizomes, that we consider a good quality, because it has the bigger size with more scales and consequently more propagules.